The Nexus of Prematurity, Birth Defects, and Intrauterine Growth Restriction: A Role for Plac1-Regulated Pathways - Fant, Michael E.; Fuentes, Juan; Kong, Xiaoyuan; Jackman, Suzanne (Frontiers in Pediatrics, 2014)
Epidemiological studies have demonstrated an increased prevalence of birth defects and intrauterine growth restriction (IUGR) among infants born prematurely suggesting they share common biological determinants. The identification of key regulatory pathways contributing to this nexus is essential to ongoing efforts to develop effective intervention strategies. Plac1 is a paternally imprinted and X-linked gene that conforms to this paradigm. Examination of a mutant mouse model has confirmed that Plac1 is essential for normal placental development and function. Moreover, it is expressed throughout the developing embryo indicating it also has broad relevance to embryogenesis. Most notably, its absence in the developing embryo is associated with abnormal brain development and an increased risk of lethal, postnatal hydrocephalus identifying it as a novel, X-linked determinant of brain development. The essential and non-redundant roles of Plac1 in placental and neurological development represent a novel regulatory paradigm for embryonic growth and pregnancy maintenance. Regulatory pathways influenced, in part, by Plac1 are likely to contribute to the observed nexus of IUGR, prematurity, and birth defects.